Frequency-Time Diagram оf Partial Discharge Pulses Recorded оn Large Generators - Kartalovic, Nenad M; Žigić, Aleksandar; Babić, Blagoje (Proceedings, Electrical engineering institute "Nikola Tesla", 2015)
This paper analyses the use of equivalent frequency-equivalent time diagram (FT diagram) of partial discharge (PD) pulses, regarding voltage and charge pulses. The described approach is widely used for large generators insulation testing purposes. For sake of clarity the certain types of partial discharge phenomena in insulation of electric machines are described and explained. The contemporary FT analysis of PD pulses is based on equivalent frequency and equivalent pulse time width derived by signal processing techniques and calculations. The numerical simulation derived and experimentally derived results are compared and evaluated for each kind of PD pulses (voltage or charge pulses). Next, the high voltage (HV) device with distributed parameters connected to HV voltage source is simulated. The parameters used in the simulation correspond to one real large synchronous generator. The obtained results lead us to the conclusion that the processing of the strain of PD charge pulses gives much more accurate results than the processing of the strain of PD voltage pulses. The experiment conducted on a large hydro generator confirmed the previous conclusions. At a same time, the sources of recorded results dispersion are shown and explained.